Twenty-First-Century Organizations: Business Firms, Business Schools, and the Academy - Hitt, Michael A. (Academy of Management Review, 1998)
The article presents a 1997 Presidential Address, “Twenty-first-century Organizations: Business Firms, Business Schools, and the Academy,” by Michael A. Hitt of Texas A&M University. The author refers to the Academy of Management, business education, technology, strategic planning, and innovation adoption.